2015
DOI: 10.4103/2230-8229.163034
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practice of schoolteachers towards students with epilepsy in Khamis Mushate, Southern Saudi Arabia

Abstract: Objectives:Epilepsy is a very common chronic neurological disorder in children throughout the world. This study was conducted to assess Saudi male schoolteachers’ knowledge of epilepsy and practice in Southern Saudi Arabia.Subjects and Methods:A cross-sectional descriptive study was conducted among male teachers; 315 teachers filled a well-designed and pretested self administered questionnaire.Results:Approximately three-quarters (72.7%) of the schoolteachers had witnessed epileptic fits. Forty-six percent bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
39
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 22 publications
7
39
6
1
Order By: Relevance
“…This attitude appears to be mainly based on the teachers" belief that epileptic students had normal mental and learning abilities. 20,36 We did not find significant association between the attitude of teachers and gender. For age, the highest percentage of teachers who were willing to provide first aid during epileptic fits was in those above 45 years old with statistical significance.…”
contrasting
confidence: 68%
See 4 more Smart Citations
“…This attitude appears to be mainly based on the teachers" belief that epileptic students had normal mental and learning abilities. 20,36 We did not find significant association between the attitude of teachers and gender. For age, the highest percentage of teachers who were willing to provide first aid during epileptic fits was in those above 45 years old with statistical significance.…”
contrasting
confidence: 68%
“…Also, it is rooted in the culture of many Arabic countries that possession by "Jinn" could result in convulsions and disturbed consciousness which are the manifestations of epileptic fit [29][30][31] A positive point was that almost all teachers in the present study (except for two) agreed that epilepsy is not contagious. In line with this finding, a study in Khamis Mushate, KSA found that most schoolteachers (82.2%) believed that epilepsy was not infectious 20 . Also, studies in Turkey, 23 Korea, 22 and India 24 found only a small percentage of participating teachers (0.6 -3.3%) who believed epilepsy to be infectious.…”
Section: Discussion:-mentioning
confidence: 59%
See 3 more Smart Citations